Psychological aspects of bruxism in children (Research, Society and Development, 2022)
Bruxism is characterized by being a repetitive muscular activity of the masticatory muscles that is designated as clenching or regimentation of the teeth or by the forced maintenance of the jaw. Assessing which disorders or personality are involved in the etiology of day and night bruxism becomes important. Scientific research has pointed out that children have often been affected by this disorder, generating harmful effects on the psychological scope of these patients. Therefore, this study aimed to describe the prevalence of bruxism in children. For a better understanding of this topic, we sought to understand its psychological impact on patients. Regarding the method, the study had a descriptive character of literature review. We searched for articles available in the Virtual Health Library (VHL), Latin American and Caribbean Literature on Health Sciences (LILACS) and Scientific Electronic Library Online (SciELO) databases, in addition to Google Scholar. Data collection took place between July and August 2022. The search resulted in 25 articles, which after using the inclusion and exclusion criteria, 14 articles remained for analysis, interpretation and discussion. In the results found, there was a significant relationship between depression, anxiety, stress and daytime bruxism. Nocturnal bruxism was associated solely with anxiety and stress.